EVALUATION AND COMPARATIVE ANALYSIS OF ROUTING ALGORITHMS FOR HOMOGENEOUS WIRELESS SENSOR (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Evaluation and comparative analysis of routing algorithms for homogeneous wireless sensor networks is a complex scientific field. Currently, this scientific work is being carried out in several countries, various design methods are being developed and put into practice. Wireless sensor nodes (SNS) consume energy for transmission, message processing, and computation. The article discusses such issues.